Examinations under anaesthesia as a measure of disease burden in unilateral retinoblastoma: the London experience. Issue 1 (12th March 2019) - Fabian, Ido Didi; Shah, Vishal; Kapelushnik, Noa; Naeem, Zishan; Onadim, Zerrin; Price, Elizabeth; Chowdhury, Tanzina; Duncan, Catriona; Stansfield, David; Sagoo, Mandeep; Reddy, Maddy Ashwin
Abstract : Background: Early diagnosis strategies and advances in retinoblastoma (Rb) management have resulted in nearly 100% survival. More attention should, therefore, be given to quality of life considerations. We aimed to quantify the number of examinations under anaesthesia (EUAs) in a cohort of patients with Rb, as a measure of disease burden. Methods: A retrospective analysis of patients with unilateral Rb that presented to the London Rb service from 2006 to 2013, were treated and had long-term follow-up. Correlations of clinical variables to number of EUAs were investigated. Results: A total of 107 patients with Rb were included that presented at a mean age of 26.51 ± 22.68 months. The International Intraocular Retinoblastoma Classification (IIRC) was group B in 5 (5%), C in 13 (12%), D in 48 (45%) and E in 41 (38%) of the cases. Primary treatment was intravenous chemotherapy in 36 (34%) and enucleation in 71 (66%) of the cases. Mean number of EUAs was 20.67 ± 6.62, 12.52 ± 6.23 and 11.15 ± 6.91 for combined groups B/C, group D and group E patients (p < 0.001), respectively. On analysis, early age atpresentation and conservative treatments were found to significantly correlate with increased number of EUAs (p < 0.001). Mean follow-up time was 74.42 ± 25.16 months and no metastasis or death were reported. Conclusion: Families should be counselled regarding the number of EUAs associated with the patient's IIRC group, with B/C eyes undergoing twice the number as compared with D/E eyes. For group D cases, where both enucleation and conservative therapy are valid options, treatment choice has a significant impact on the number of EUAs.